Hubungan Family Support Dengan Tingkat Kecemasan Ibu Hamil Primigravida Trimester Iii Di Desa Kaliboto Puskesmas Tarokan - Wahyuningsih, Diyan (Sekolah Tinggi Ilmu Kesehatan Adila Bandar Lampung, 2025)
Pregnancy is an important phase in a woman's life, especially for primigravida entering the third trimester. Physical and emotional changes experienced can trigger anxiety. Family support is an important factor in reducing anxiety during pregnancy. This study aims to analyze the relationship between family support and the level of anxiety of primigravida pregnant women in the third trimester in Kaliboto Village, Tarokan Health Center. This study used a quantitative method with a cross-sectional research design. The sample in this study were primigravida pregnant women in the third trimester who were in Kaliboto Village and registered at the Tarokan Health Center. The sampling technique used simple random sampling. Data were collected through a questionnaire consisting of a family support scale and a Hamilton Anxiety Rating Scale (HARS) anxiety scale. Data analysis was carried out using the Pearson/Spearman correlation test according to the data distribution. The results of the study showed that there was a significant relationship between family support and the level of anxiety of primigravida pregnant women in the third trimester (p < 0.05). Pregnant women who received high family support tended to have lower levels of anxiety.